2017
DOI: 10.1002/aur.1767
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble perception in autism spectrum disorder: Member‐identification versus mean‐discrimination

Abstract: To efficiently represent the outside world our brain compresses sets of similar items into a summarized representation, a phenomenon known as ensemble perception. While most studies on ensemble perception investigate this perceptual mechanism in typically developing (TD) adults, more recently, researchers studying perceptual organization in individuals with autism spectrum disorder (ASD) have turned their attention toward ensemble perception. The current study is the first to investigate the use of ensemble pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…It should also be noted that our results here pertain directly to ensemble processing of the size of objects in an array, and these results may not generalize to ensemble processing of all types of stimulus features. Though these results are similar to previous findings of decreased ensemble processing of size, color, and facial identity (Corbett et al 2016;Maul et al, 2016;Rhodes et al, 2014;Van der Hallen et al, 2017), this decrease was not observed with ensemble processing of emotional expression (Karaminis et al, 2017) or with more homogeneous arrays (Van der Hallen et al, 2017). As such, future research incorporating multiple measures of ensemble processing across an array of stimulus features would be quite beneficial.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It should also be noted that our results here pertain directly to ensemble processing of the size of objects in an array, and these results may not generalize to ensemble processing of all types of stimulus features. Though these results are similar to previous findings of decreased ensemble processing of size, color, and facial identity (Corbett et al 2016;Maul et al, 2016;Rhodes et al, 2014;Van der Hallen et al, 2017), this decrease was not observed with ensemble processing of emotional expression (Karaminis et al, 2017) or with more homogeneous arrays (Van der Hallen et al, 2017). As such, future research incorporating multiple measures of ensemble processing across an array of stimulus features would be quite beneficial.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with ASD are able to represent some level of ensemble information, but this representation may be compromised when compared to TD individuals (Corbett, Venuti, & Melcher, 2016;Maul, Stanworth, Pellicano, & Franklin, 2016;Rhodes, Neumann, Ewing, & Palermo, 2014), though experimental variables such as ensemble heterogeneity may influence this effect (Van der Hallen et al, 2017). The results of the present study expand these latter findings to suggest that these findings are not constrained to individuals with a clinical diagnosis, but can also be observed in the general population relative to their individual level of autistic traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also of interest to investigate this phenomenon in ASC since they are known to process human faces differentially 23,24 , with well-documented delays in the latency of N170 event-related potentials in response to faces 25 . Furthermore, while deficits have been found to occur, at least in low-level global summarizing abilities 26,27 , this has been contradicted 28 . Nonetheless, idiosyncrasies concerning ASCs' visual processing/perception and the possible implications of such perceptual biases regarding differences in visually guided cognition have been suggested 29 and atypical perception is included as a recent diagnostic criterion for ASC as per the Diagnostic and Statistical Manual of Mental Disorders (DSM)-V 30 .…”
mentioning
confidence: 99%
“…Our results, showing no increased discrimination performance for within-category phonemic variants or for stimuli when presented as nonspeech stimuli, do not support this second account either. We should note here that in other domains, including the visual domain for which the first Bayesian accounts were proposed, evidence in favor of these two accounts is highly contradictory [e.g., Pell et al, 2016;Van der Hallen, Lemmens, Steyaert, Noens, & Wagemans, 2017]. A third account considers that prior knowledge once acquired will normally influence performance in perceptual task, but if the structure of perceptual information changes, people with autism have difficulties in accurately updating prior knowledge with the new perceptual regularities [Van de Cruys et al, 2014].…”
Section: Discussionmentioning
confidence: 98%